Handbook of research on global competitive advantage through innovation and entrepreneurship - Farinha, Luis M. Carmo, 1975-; e; Lawton Smith, Helen; Bagchi-Sen, Sharmistha, 1961-; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2015)
"This book explores the emergence of new ideas and opportunities in various markets and provides organizational leaders with the tools they need to take full advantage of those opportunities, focusing on economic growth in a fast-paced environment"--Provided by publisher.
Global competitive advantage -- Regional innovation systems and competitiveness -- Competitiveness and clusters -- Knowledge, technology, and innovation -- Entrepreneurship and internationalization -- Entrepreneurial strategy and value creation.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 06/18/2015).
Keywords: Competition; Technological innovations -- Economic aspects; Entrepreneurship; Economic development; Competitive agility; Cultural capital; Global competitiveness; International entrepreneurship; New product development; Regional development; Social entrepreneurship; Socio-economic behavior; Sustainable business; Workload control; Electronic books